2018
DOI: 10.1371/journal.pone.0197143
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and sex behaviour in pregnancy and breastfeeding in high HIV prevalence settings: Programmatic implications for PrEP delivery

Abstract: HIV acquisition during pregnancy and breastfeeding significantly contributes toward paediatric HIV infection; however, little is known about risk behaviours in HIV-uninfected pregnant and postpartum women. We conducted twenty-six in-depth-interviews between July and December 2016 using a semi-structured interview guide among HIV-uninfected pregnant and recently postpartum women at-risk of HIV acquisition (defined as reporting ≥1 of the following: partner’s serostatus unknown or HIV-infected, recent condomless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Despite these favorable opinions, the reported concerns among respondents require consideration, particularly in the design of future programs. For example, concerns about potential harm to mother and infant echo findings from other studies in the region [4, 32, 33]. Similar to other settings [30, 34], the need for near-perfect adherence raised concerns and participants worried about the consequences of HIV transmission in the context of poor PrEP adherence.…”
Section: Discussionmentioning
confidence: 83%
“…Despite these favorable opinions, the reported concerns among respondents require consideration, particularly in the design of future programs. For example, concerns about potential harm to mother and infant echo findings from other studies in the region [4, 32, 33]. Similar to other settings [30, 34], the need for near-perfect adherence raised concerns and participants worried about the consequences of HIV transmission in the context of poor PrEP adherence.…”
Section: Discussionmentioning
confidence: 83%
“…There is a dearth of data on PrEP uptake and adherence in pregnant/breastfeeding women [9,19]. A recent study in pregnant and postpartum SA women found that there was a high potential interest in PrEP during pregnancy, though baseline knowledge was low [36].…”
Section: Discussionmentioning
confidence: 99%
“…We examined crude associations between possible confounders (gestational age at baseline, education level, gravidity, partner HIV testing, STI at baseline), exposures (internalized PrEP stigma and anticipated PrEP stigma) and outcomes of interest ((1) PrEP care initiation at baseline, (2) PrEP care retention at three months, (3) PrEP care continuation at three months and (4) Self-reported PrEP adherence at three months) in separate models using logistic regression. We chose these variables based on formative research on PrEP use among pregnant women in South Africa [ 5 , 6 ]. We considered exact logistic regression but did not find significant differences in the results.…”
Section: Methodsmentioning
confidence: 99%